THE RELATIONSHIP BETWEEN ACADEMIC STRESS AND ACADEMIC PERFORMANCE AMONG UNISEL STUDENTS - Mohamad Asri, Muhammad Faris Mirza; Zulkanain, Nuramira Elyana Binti; Mohammad Izani, Nur Izzana Binti; Kasim, Nur Muneerah Binti (Selangor Humaniora Review, 2024)
Academic pressure refers to the various challenges faced by students at different levels of education that arise from the demanding nature of academia. These challenges include the pressure to meet high standards, achieve academic success and manage a heavy workload. The lack of research on the relationship between academic stress and its impact on academic performance presents a complex issue. Therefore, this study aims to investigate the relationship between academic pressure and academic performance. A quantitative research design was used in which 100 undergraduate students participated. Convenience sampling was used to select the respondents. Data were collected using self-administered questionnaires consisting of 18 items adapted from the Perceived Stress Scale (PSS) and the Academic Performance Scale (APS). The statistical software SPSS was used to analyse the data. The results showed no significant relationship between academic stress and academic performance in university students. This study provides valuable insights for future researchers and stakeholders and helps to improve the understanding of stress-related issues that specifically affect university students.